Study of hardness and tensile strength of Aluminium-7075 percentage varying reinforced with graphite and bagasse-ash composites - Mohammed Imran; Anwar Khan A. R.; Sadananda Megeri; Shoaib Sadik (2016, 2016)
Title screen